Genesis of the Abunabu antimony deposits in the Tethys Himalayan metallogenic belt: Evidence from He–Ar and S isotopes of stibnite - Li, Yang; Wang, Chenghui; Li, Yubin; Sun, Yan; Puchi, Mima; Zhang, Xudong; Lamu, Gesang; Yang, Zong (Frontiers in Earth Science, 2023)
The Abunabu antimony mining area is located between the Indus–Yarlung Tsangpo suture and the southern Tibetan detachment system. Ore deposits in the mining area provide an excellent opportunity to understand the nature and genesis of antimony mineralisation in the Tethys Himalayan metallogenic belt. In this study, we analysed the He–Ar and S isotopic compositions of stibnite-hosted fluid inclusions as a basis for investigating the sources of ore-forming fluids in the Abunabu mining area and the Tethys Himalayan metallogenic belt. The analysed stibnites have 4He contents of 0.016 × 10−7–1.584 × 10−7 cm3 STP/g, 40Ar contents of 1.37 × 10−7–2.94 × 10−7 cm3 STP/g, 40Ar/36Ar ratios of 303.8–320.7, and 3He/4He (Ra) ratios of 0.021–0.351. These isotopic features indicate that the ore-forming fluids were primarily metamorphic fluids of crustal origin, with small amounts of magmatic-derived materials and modified air-saturated water with low 40Ar*/4He ratios. The δ34S values of stibnite vary within a narrow range of −4.9‰ to −3.5‰, with a mean value of −4.31‰, indicating a deep magmatic origin. On the basis of these results and a compilation of data for sulphide deposits in the metallogenic belt, we infer that compositional variations in the He and Ar isotopes of the ore-forming fluids of each antimony deposit in the Tethys Himalayan metallogenic belt are independent of each other. This suggests that antimony deposits in the belt had similar ore-forming fluid sources and mixing processes and that differences in the metallogenic tectonic setting within the belt emerged only in the later stages of deposit evolution. Our new results and compiled data also show that antimony–gold deposits and lead–zinc–antimony polymetallic deposits in the Tethys Himalayan metallogenic belt differ in their sulphur isotopic compositions and that multiple sulphur sources were involved in each of these types of deposit.